Portable sauna stimulated-diaphoresis for the treatment of fluid-overload in peritoneal dialysis patients: A pilot study - Maggiani-Aguilera, Pablo; Chávez-Iñiguez, Jonathan S.; Navarro-Blackaller, Guillermo; Hernández-Morales, Karla; Geraldo-Ozuna, Ariadna Lizbeth; Alcantar-Villín, Luz; Montoya-Montoya, Olivia; Luquín-Arellano, Víctor Hugo; García-García, Guillermo (Frontiers in Medicine, 2022)
Background: Fluid overload (FO) is a common problem in patients on peritoneal dialysis (PD), it is associated with adverse outcomes, and may persist despite adjustments in PD therapy. Objective: To evaluate the feasibility and safety of stimulated diaphoresis to reduce FO with the use of a portable sauna bath. Methods: Open-label pilot study in patients on continuous ambulatory peritoneal dialysis (CAPD) and FO. The primary outcome was the treatment-related adverse events; secondary outcomes were changes in over-hydration (OH), body weight and blood pressure, FO symptoms, and sleep quality. Dialysis prescription and daily data were recorded. The intervention period consisted in a 30-minute, 45° C sauna bath, daily for 10 days, using a portable sauna bath. Results: 51 out of 54 total sauna bath sessions were well tolerated. In 3 (5.5%) sessions adverse effects were reported: transient dizziness in two cases, and a second-degree skin burn in a patient with advanced diabetic neuropathy. OH (6.3 ± 1.2 L vs 5.5 ± 1.3 L, p = 0.05), body weight (67.7 ± 11.4 vs 66.8 ± 3.8 kg, p = 0.003), diastolic blood pressure (92 ± 13.5 vs. 83 ± 13.3 mmHg, P = 0.003) and PSQI score (7.3 +- 3.7 vs. 5.1 +- 3.2, p = 0.02) improved significantly between the control and intervention period, respectively. Conclusions: Stimulated diaphoresis with a portable sauna bath could be a novel, safe, and effective alternative way to reduce FO in CAPD patients. Larger studies are needed to confirm our results.